PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN PENINGKATAN DISIPLIN KERJA GURU TERHADAP PRESTASI BELAJAR SISWA SMK NEGERI 1 BALONGAN KABUPATEN INDRAMAYU - Hanan, Abdul; Syihabudin, Abu (Pascasarjana Unviersitas Majalengka, 2022)
Headteacher leadership, work motivation is a factor in improving work discipline. The motivation factor becomes one that affects the teacher's work discipline in improving its quality because the more motivation a person is more likely to improve his work discipline. This work motivation causes a teacher to be passionate in carrying out duties as an educator because it has fulfilled his needs. The fulfillment of these needs is related to job satisfaction, where among the expectations of teachers are met by the reality provided by the organization. This research method uses descriptive methods of analysis, which look at the relationship between two or more variables through the analysis of the data obtained. This method is also often called descriptive verifiive analysis because it looks for how much influence leadership and work discipline have on students' learning achievement. The results of the study proved that the leadership of the principal has a positive and significant effect on learning achievement. The discipline of the teacher's work has a positive and significant effect on learning achievement. Headteacher leadership and teacher work discipline simultaneously have a positive and significant effect on learning achievement